Pengetahuan dan sikap perawat tentang kode etik keperawatan - Rifai, Ahmad; Afandi, Alfid Tri; Firmansyah, Irfan (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2023)
Background: The nursing code of ethics is an obligation for every nurse to apply it, in applying the nursing code of ethics as if it is binding on legal provisions that are binding. The application of the nursing code of ethics is a principle for providing quality nursing services for patients and this is needed for nurses in various positions to commit to the nursing profession. The purpose of applying the code of ethics is to identify, organize, examine and justify humanitarian actions by applying the principles of the nursing code of ethics. Purpose: The purpose of this study was to find out the description of knowledge and attitude of nurses about the code of ethics of nursing in the Kalisat Regional Hospital, Jember Regency. Methods: This research uses descriptive research design with sampling technique which is total sampling with 82 respondents. Retrieval of data using a questionnaire of nurses' knowledge and attitudes about the nursing code of ethics. Results: The results obtained showed 82 (100%) respondents had knowledge of the nursing code of ethics in the good category and 69 (84.1%) had an attitude about the code of ethics in the good category. Although most of the nurses 'knowledge and attitudes about the nursing code of ethics are in the good category, there are several indicators of nurses' knowledge and attitude about the code of ethics in the moderate and less categories. With advances in health technology, nurses must always improve nurses' knowledge and attitudes about the nursing code of ethics in order to improve the quality of providing nursing care in accordance with the guidelines for the nursing code of ethics. Knowledge possessed by a nurse can influence the nurse's way of thinking so that the nurse indirectly forms a good attitude in applying the nursing code of ethics. Conclusion: These results indicate the nurses' knowledge and attitudes about the nursing code of ethics in the good category but in each indicator there are still nurses who have moderate knowledge and attitudes that need to be improved for maximum results on each indicator. Keywords: Knowledge; Attitudes; Code of Ethic; Nurse; Nursing. Pendahuluan: Kode etik keperawatan adalah sebuah kewajiban bagi setiap perawat untuk menerapkannya, dalam menerapkan kode etik keperawatan layaknya menjelankan ketentuan hukum yang bersifat mengikat. Penerapan kode etik keperawatan adalah prinsip untuk memberi pelayanan keperawatan yang berkualitas bagi pasien dan ini di perlukan bagi perawat di berbagai posisi untuk berkomitmen pada profesi keperawatan. Tujuan penerapan kode etik untuk mengidentifikasi, mengorganisasikan, memeriksa dan membenarkan tindakan- tindakan kemanusiaan dengan menerapkan prinsip-prinsip kode etik keperawatan. Tujuan: Mengetahuai gambaran pengetahuan dan sikap perawata tentang kode etik keperawatan di Rumah Sakit Daerah Kalisat Kabupaten Jember. Metode: Penelitian ini menggunakan desain penelitian deskriptif dengan teknik pengambilan sampel yaitu sampling total dengan jumlah responden 82 perawat. Pengambilan data menggunakan kuesioner pengetahuan dan sikap perawat tentang kode etik keperawatan. Hasil: Hasil penelitian yang di peroleh menggambarkan 82 (100%) responden memiliki pengetahuan tentang kode etik keperawatan dalam kategori baik. Seorang perawat sangat penting untuk memahami pedoman kode etik keperawatan karena kode etik keperawatan merupakan pedoman dalam melakukan pelayanan keperawatan dan 69 (84,1%) memiliki sikap tentang kode etik dalam kategori baik, 13 (15,9%) responden memiliki sikap tentang kode etik keperawatan dalam kategori sedang. pengetahuan yang dimiliki seorang perawat dapat mempengaruhi cara berfikir perawat tersebut sehingga secara tidak langsung perawat tersebut membentuk sikap yang baik dalam menerapkan kode etik keperawatan. Simpulan: Hasil tersebut menunjukkan pengetahuan dan sikap perawat tentang kode etik keperawatan dalam kategori baik namun pada setiap indikator yang masih terdapat perawat yang memiliki pengetahuan dan sikap sedang dan kurang perlu di tingkatkan untuk hasil yang maximal pada setiap indikator. Kata Kunci: Pengetahuan; Sikap; Kode Etik, Perawat, Keperawatan